Efek Orabase Kombinasi Ekstrak Daun Salam (Syzygium Polyanthum (Wight) Walp.) dan Asam Hialuronat Terhadap Penyembuhan Ulser Traumatik Mukosa Mulut pada Tikus Wistar - Tarisa Yunita Lathifunda (Fakultas Kedokteran Gigi, 2026)
Oral traumatic ulcers are a common condition that impairs eating and speaking, diminishing patient quality of life. Healing is often slow due to the oral cavity's moist environment. The study investigated a therapeutic combination of bay leaf (Syzygium polyanthum) extract and hyaluronic acid. The bay leaf extract contributes anti-inflammatory and tissue-promoting properties, whereas hyaluronic acid supports regeneration by hydrating tissue and facilitating fibroblast migration. An experimental post-test only control group design was employed using 36 Wistar rats with thermally induced ulcers. They were divided into negative control, positive control, and treatment groups. Ulcer diameter was measured on days 3, 6, and 9 using a UNC-15 probe. Data were analyzed with Shapiro–Wilk, Levene, ANOVA, LSD, Kruskal–Wallis, and Mann–Whitney tests. The treatment group showed the most significant wound diameter reduction, achieving complete healing by day nine. Statistically significant differences (p < 0.05) were found compared to the negative control on all observation days. The findings demonstrate that the combination of bay leaf extract and hyaluronic acid in orabase effectively accelerates ulcer healing through anti-inflammatory and tissue-regenerative mechanisms.
:: Finalisasi Repositori File 3 Juni 2026_Kurnadi
Keywords: bay leaf extract; hyaluronic acid; orabase; traumatic ulcer